Learning from Experience and Learning from Others: An Exploration of Learning and Spillovers in Wartime Shipbuilding - Thornton, Rebecca Achee; Thompson, Peter (American Economic Review, 2001)
A new data set facilitates study of learning spillovers in World War II shipbuilding. Our results contain two principal but contrasting themes. First, learning spillovers were a significant source of productivity growth, and may have contributed more than conventional learning effects. Second, the size of the learning externalities across yards, as measured by Spence's θ, were small. These findings, which are not mutually inconsistent, suggest an optimistic view of learning spillovers: they are a significant source of productivity growth, but the market failures induced by learning externalities may be modest. (JEL D24, N72, O3)